Abiotic factors controlling the establishment and abundance of the invasive golden mussel Limnoperna fortunei - Oliveira, Márcia D; Calheiros, Débora F; Jacobi, Claudia M; Hamilton, Stephen K (Biological invasions, 2011)
Limnoperna fortunei (Bivalvia, Mytilidae), a freshwater bivalve native to Southern Asia, has been an invasive species in South America since 1991. It spread upstream in the La Plata basin reaching the Paraguay River in the vicinity of the Pantanal wetland, Brazil, around 1998. The role of abiotic factors in controlling establishment and abundance of this species is not well known, making projections of its risk of further spread difficult. This study evaluates the importance of abiotic factors to L. fortunei populations established in rivers of the Pantanal, focusing on larval and juvenile densities and taking advantage of a wide range of seasonal variability in water temperature, flow, dissolved oxygen, and suspended material. Temperature, river stage (influencing several water characteristics) and water velocity are the main variables related to the larval and juvenile densities. In the Pantanal, environmental variables vary over a broader range compared with other South American locations, subjecting L. fortunei to oxygen depletion, low calcium, low pH, and high water velocity and suspended solids, associated with low chlorophyll a concentrations. The combined effect of several of these conditions may explain the relatively low densities in some Pantanal sites. However, they probably will not prevent the persistence of populations in the Pantanal and the eventual establishment of viable populations in upriver systems connected to the Pantanal. These results are pertinent not only to this species but also to other aquatic invasive invertebrates whose expansion may be limited by thermal extremes, episodic oxygen depletion, and waters that are too dilute or acidic for optimal biocalcification.